Bombesin-like Peptides Modulate Alveolarization and Angiogenesis in Bronchopulmonary Dysplasia - Subramaniam, Meera (American Thoracic Society, 2007)
Rationale: The incidence of bronchopulmonary dysplasia (BPD), a chronic lung disease of newborns, is paradoxically rising despite medical advances. We demonstrated elevated bombesin-like peptide levels in infants that later developed BPD. In the 140-day hyperoxic baboon model of BPD, anti-bombesin antibody 2A11 abrogated lung injury. Objectives: To test the hypothesis that bombesin-like peptides mediate BPD in extremely premature baboons (born at Gestational Day 125 and given oxygen pro re nata [PRN], called the 125-day PRN model), similar to “modern-day BPD.” Methods: The 125-day animals were treated with 2A11 on Postnatal Day 1 (P1), P3, and P6. On P14 and P21, lungs were inflation-fixed for histopathologic analyses of alveolarization. Regulation of angiogenesis by bombesin was evaluated using cultured pulmonary microvascular endothelial cells. Measurements and Main Results: In 125-day PRN animals, urine bombesin-like peptide levels at P2–3 are directly correlated with impaired lung function at P14. Gastrin-releasing peptide (the major pulmonary bombesin-like peptide) mRNA was elevated eightfold at P1 and remained high thereafter. At P14, 2A11 reduced alveolar wall thickness and increased the percentage of secondary septa containing endothelial cells. At P21, 2A11-treated 125-day PRN animals had improved alveolarization according to mean linear intercepts and number of branch points per millimeter squared. Bombesin promoted tubulogenesis of cultured pulmonary microvascular endothelial cells, but cocultured fetal lung mesenchymal cells abrogated this effect. Conclusions: Early bombesin-like peptide overproduction in 125-day PRN animals predicted alveolarization defects weeks later. Bombesin-like peptide blockade improved septation, with the greatest effects at P21. This could have implications for preventing BPD in premature infants.